Solidarity and freedom Japanese-style, or some lessons on social order - Filina, Iryna (Actual Problems of Mind, 2017)
The paper explicates some sources of a specific spiritual solidarity of Japanese people and explains their understanding of freedom. The author points out that Japanese people demonstrate an interesting and original way of the social order construction which may be very useful for Ukrainians.